Writing Władysław Gomułka's Life: Historiography of Władysław Gomułka's Biographies. Issue 3 (August 2022) - Müller, Anna
This article looks at a select number of biographies of Władysław Gomułka—an important postwar Polish politician, who because of his long presence in politics is often perceived as the de facto Polish postwar leader. He served in multiple roles: parliamentary deputy, deputy prime minister, minister, member of the Council of State, and the First Secretary of the communist party. I argue that for historians who take up the task of writing his biography, Gomułka is more than a historical figure, and that writing about him allows them to ponder the question of agency and historical contingencies, as well as the meaning of the past for the present. Not surprisingly, Gomułka's biography serves as a form of a meta-commentary on contemporary approach to the Communist history and its place in Polish history. The existing biographies contain reflections, even if indirectly, on the nature of Communism in Poland, not as elements of the past but as aspects of the present that loom over the future. By the same token, the lack of interest in Gomułka at certain important historical junctures, or a rather selective interest, indicates not as much a lack of interest in an important politician, but rather a certain skewed interest in Communism—not just its shortcomings, but also its potential benefits. The silence gives a certain perception of Communism as something pushed to the margins.